Impact of various types of soybean cake to soy straw briquettes on the heat of briquette combustion - Wcisło, G.; Pracuch, B.; Łagowski, P.; Kurczyński, D.; Tomyuk, V. (University of Engineering and Economics in Rzeszow, 2019)
The paper presents results of research demonstrating the effects on heat of combustion of adding press cake from three varieties of soyben Erica, Mavka and Sirelia to soyben stalk based briquette. The conducted research shows that heat of combustion of soyben stalk was 15.2 [MJ∙kg-1], much lower than the heat of combustion of press cake from four. Press cake heat of combustion from the most effective Erica soyben variety was 23.4 [MJ∙kg-1], or 54 % (w/w) more than that of rape stalk. Press cake heat of combustion from the least effective soyben variety was 19.8 [MJ∙kg-1], or 30 % (w/w) more than that of soyben stalk. Adding 20 % (w/w) of press cake during briquette production Erica varieties resulted in an increase in heat of combustion by approximately 10.5; and a 40 % (w/w) addition resulted in a further increase of approximately 20.4 %, a 60 % (w/w) addition of press cake increased heat of combustion by approximately 31.6 whereas an 80 % (w/w) press cake content increased heat of combustion by more than 38.8 %.
Keywords: briquette; soyben stalk; press cake; heat of combustion